Pernas no meio do caminho: o feminino na poética de O amor natural de Carlos Drummond de Andrade - Varela, Larissa Rizzi (2024)
O amor natural, a posthumous book of erotic poems by Carlos Drummond de Andrade, awakens deep reflections on sex, eroticism, and love, it also incites considerations regarding the voice and role that the female figure plays in these scopes. Thus, this research aims to analyze the female representations in the lustful scenes of this work, examining whether the images associated with them reproduce the phallocentric logic that has maintained, since the licentious literary tradition of Greco-Roman Antiquity, violation and hierarchy as natural attributes of heterosexual erotic-amorous relationships. To do so, it studies the association between eroticism, sexuality, love, and the feminine, and in the reading of lustful texts dated from Greco- Roman Antiquity to the 19th century, traces of such logic are found in portraying the feminine in the erotic game. The bibliographic and qualitative research conducts exploratory survey of these themes and is based on the studies of George Bataille (2014), Octavio Paz (1994), Alexandrian (1993), Richard Shusterman (2021), and José Paulo Paes (2006). Next, it evaluates if something similar occurred in the connection between Brazilian Modernism and eroticism and, more specifically, how Drummond related to sexual fervor in the 1970s and 1980s, a time when some poems from O amor natural were sporadically published. This was done through studies by Eliane Robert Moraes (2008-2015-2022), Mary Del Priore (2011), Rita de Cassia Barbosa (1987), Jesus Antônio Durigan (1986), and consulting copies of men's magazines Status (1983-1984) and Ele & Ela (1983). Finally, it investigates the trajectory of Drummond's erotic-amorous poetry with the help of the writings of Affonso Romano de Sant’Anna (2011) and Mirella Vieira Lima (1995); by proposing a reading of the poems from O amor natural, it engages in a dialogue between the content presented in the first two moments, analyzing how social issues related to the sexual revolution and the female freedom erupt in the content and form of the poems, but also identifies how traces of images derived from the Western erotic literary tradition remain. In general terms, it is understood that, accompanying the winds of the sexual revolution, the female figure is portrayed positively in the active pole of the erotic scenes of O amor natural, the sexual practices that she engages in provide the couple with a transcendental ecstasy. However, the voice of a male poetic subject predominates who, in the middle of the poems, even breaks with the old logic of the erotic game (violator/violated), but, at the end of the texts, seeks conciliation and limits the masculine and feminine poles again to these roles. Thus, domination and hierarchy still seem to be “natural” attributes of erotic-amorous relationships. This stance seems to be related to the tensions of the sexual fervor of the 1970s and 1980s in Brazil, where there was a desire to freely experiment with pleasure, whether in the body or in words, but the full realization of this desire in Drummond's poetry still clashes with the intrinsic male structure.